Death Penalty: A Response to Arguments by Indonesian Muslim Opposers - Muchammad Ichsan (Jurnal Hukum Novelty, 2020)
Introduction to The Problem: Life is the greatest gift human beings receive. Man can achieve any task with life, and without it, man can do nothing. Thus, attempts by the State to punish human beings with the death penalty for wrongdoing are reaping the pros and cons. It is clear the stance of Western human rights activists opposed to the death penalty. What is interesting is that, although Islamic law supports it, many educated Muslims have objected to the death penalty.Purpose/Objective Study: The purpose of this research is to analyze and respond to the arguments used by Indonesian Muslim human rights activists, especially those integrated into human rights organizations, which are anti-death penalty. It is hoped that these reviews and responses will contain more definite opinions that can provide enlightenment for all.Design/Methodology/Approach: This research used a descriptive, analytical approach. Therefore, it employed secondary data and normative methods combined to case and statute approach in studying, analyzing, and responding to the arguments of anti-death penalty human rights activists among Indonesian Muslims. Their cases are to be brought forward, investigated, and then returned one by one.Findings: The research found that the human rights ideology propagated by western human rights activists is influencing Indonesian Muslim activists. They have the same point that the death penalty degrades humanity and violates human rights. In the meantime, Islamic law defends the death penalty for providing justice to the victims and the wider community, and for preserving life.